Fampridine and Acetazolamide in EA2 and Related Familial EA: A Prospective Randomized Placebo-Controlled Trial. Issue 4 (August 2021) - Muth, Carolin; Teufel, Julian; Scho[Combining Diaeresis]ls, Ludger; Synofzik, Matthis; Franke, Christiana; Timmann, Dagmar; Mansmann, Ulrich; Strupp, Michael
Abstract : Objective: To determine the efficacy and safety of the treatment with prolonged-release 4-aminopyridine (fampridine) and acetazolamide for patients with episodic ataxia type 2 (EA2), patients with EA2 were treated with a random sequence of fampridine, acetazolamide, and placebo in a 3-period crossover trial. Methods: A total of 30 patients with EA2 (8 female; aged 20–71 years; 18 genetically confirmed, 4 with a positive family history, 8 with the clinical diagnosis) were enrolled in this phase III, randomized, double-blind, placebo-controlled, 3-period crossover trial. Each period lasted 12 weeks with a 4-week washout period. Each patient received a random sequence of 20 mg/d fampridine, 750 mg/d acetazolamide, and placebo. The primary end point was the number of attacks during the last 30 days within the 12-week treatment period. Participants, caregivers, and those assessing the outcomes were blinded to the intervention. Results: Compared with placebo, fampridine reduced the number of attacks to 63% (95% CI 54%–74%) and acetazolamide to 52% (95% CI 46%–60%). A total of 39 (26.5%) adverse events were observed under treatment with fampridine (mostly tingling paresthesia and fatigue), 66 (44.9%) happened under acetazolamide (mostly taste disturbance and gastrointestinal complaints), and 42 (28.6%) under placebo (mostly gastrointestinal complaints). Conclusion: Both fampridine and acetazolamide significantly reduce the number of attacks in patients with EA2 and related EA in comparison to placebo. Fampridine 10 mg twice daily had fewer side effects than acetazolamide 250 mg 3 times daily. The trial was registered with DRKS.de (DRKS00005258) and EudraCT (2013-000107-17). This study was supported by the Federal Ministry of Education and Research (BMBF) (grant number 01EO0901). Fampridine (study medication) was provided by Biogen Idec. Classification of Evidence: Class II evidence.